2011
DOI: 10.1093/ndt/gfr271
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 3 ligands induce CD80 expression in human podocytes via an NF- B-dependent pathway

Abstract: Activation of TLR3 on cultured human podocytes induces CD80 expression and phenotypic change via an NF-κB-dependent mechanism and is partially blocked by dexamethasone. These studies provide a mechanism by which viral infections may cause proteinuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 23 publications
3
83
0
1
Order By: Relevance
“…IFN family proteins have been implicated in the pathogenesis of focal segmental glomerulosclerosis, and TLR3 signaling in podocytes is thought to be involved in proteinuria [26]. Therefore, it is of interest to examine if TLR3 signaling regulates the expression of ISG56 in podocytes as well.…”
Section: Discussionmentioning
confidence: 99%
“…IFN family proteins have been implicated in the pathogenesis of focal segmental glomerulosclerosis, and TLR3 signaling in podocytes is thought to be involved in proteinuria [26]. Therefore, it is of interest to examine if TLR3 signaling regulates the expression of ISG56 in podocytes as well.…”
Section: Discussionmentioning
confidence: 99%
“…Recent observations have revealed that NF-κB of podocyte and peripheral blood mononuclear cells (PBMC) play an important role in the development of proteinuria in MCNS because it regulates cytokine expression, through association with other transcription factors and protein-protein interactions with coactivator proteins [5]: e.g., Shimada et al [18] reported that an activation of Toll-like receptor 3 on cultured human podocytes induces CD80 expression and phenotypic change via an NF-κB-dependent mechanism and is partially blocked by dexamethasone; Cao et al [19] postulated that the abnormal activation of NF-κB is involved in the pathogenesis of MCNS providing that its DNA-binding abilities were significantly increased in PBMC from MCNS patients compared with controls, and there were strong correlations between urinary protein and the baseline DNA-binding ability of NF-κB; Sahali et al [20] demonstrated that nuclear extracts from PBMC during relapse in patients with MCNS displayed high levels of NF-κB DNA-binding activity.…”
Section: Discussionmentioning
confidence: 99%
“…CD80 is also present in the podocytes of mice in MCD models and is necessary for resulting proteinuria. [7][8][9] Soluble urinary CD80 levels are elevated in children and adolescents with MCD in relapse compared with those individuals in remission, patients with other glomerular disease, and control subjects. 10 Furthermore, urinary CD80/creatinine ratios are increased in MCD in relapse compared with MCD in remission or FSGS.…”
Section: Pathophysiologymentioning
confidence: 99%